1997
DOI: 10.1007/s001340050344
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function in septic multiple organ dysfunction syndrome

Abstract: In septic patients platelets become activated and are hyperadhesive to other vascular cells including neutrophils and endothelium. This may induce sequestration of platelets and microcirculatory arrest, thus the development of MODS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
164
1
14

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(188 citation statements)
references
References 30 publications
(35 reference statements)
9
164
1
14
Order By: Relevance
“…Additionally, septic platelet activation can facilitate the production of both pro-and antiinflammatory cytokine networks (26). The nature of this platelet activation is characterized by increased surface Pselectin expression (27,28); increased levels of a granulereleased factors in plasma, such as soluble P-selectin (29); and increased levels of triggering receptor expressed on myeloid cells-like transcript-1 (30) or PF-4 in mice (31). Clark et al (6) also showed a novel mechanism of platelet-neutrophil interaction that leads to enhanced bacterial trapping during sepsis.…”
Section: Platelets and Pathogensmentioning
confidence: 99%
“…Additionally, septic platelet activation can facilitate the production of both pro-and antiinflammatory cytokine networks (26). The nature of this platelet activation is characterized by increased surface Pselectin expression (27,28); increased levels of a granulereleased factors in plasma, such as soluble P-selectin (29); and increased levels of triggering receptor expressed on myeloid cells-like transcript-1 (30) or PF-4 in mice (31). Clark et al (6) also showed a novel mechanism of platelet-neutrophil interaction that leads to enhanced bacterial trapping during sepsis.…”
Section: Platelets and Pathogensmentioning
confidence: 99%
“…Several studies have shown that platelet counts and function are reduced in patients with severe sepsis and septic shock (9)(10)(11). Moreover, platelet indices, such as mean platelet volume (MPV) and platelet distribution width (PDW), have been associated with these conditions (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…By using different animal models, studies have shown the indispensable role of platelets in the initiation and progression of inflammatory and autoimmune diseases, including sepsis, 12 atherosclerosis, 13 autoimmune myocarditis, 14 systemic lupus erythematosus, 15 rheumatoid arthritis [16][17][18][19] and so on. Allergic asthma is a chronic inflammatory pathological condition with critical involvement of T helper 2 (Th2) cells that is harmful to human health throughout the world.…”
Section: Introductionmentioning
confidence: 99%